2017
DOI: 10.1111/jvh.12666
|View full text |Cite
|
Sign up to set email alerts
|

HCV reinfection incidence among individuals treated for recent infection

Abstract: Background and aims One challenge to HCV elimination through therapeutic intervention is reinfection. The aim of this analysis was to calculate the incidence of HCV reinfection among both HIV-positive and negative individuals treated for recent HCV infection (estimated infection duration <18 months). Methods Individuals with recent HCV infection who achieved an end-of-treatment response in four open-label studies between 2004 and 2015 in Australia and New Zealand were assessed for HCV reinfection, confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 63 publications
(143 reference statements)
0
46
0
2
Order By: Relevance
“…More recently, a review of low and high-risk HCV mono-infected patients also treated primarily with interferon-based therapies, estimated reinfection rates of 0.19 and 2.2 per 100 PYs, respectively, although estimates in these studies ranged considerably [17]. Additional studies have reported interferon era reinfection rates that range between 4.9 and 15.5 per 100 PYs for those with ongoing injection exposure following treatment [18,28,29]. We recently reported reinfection rates of 1.00 and 2.11 per 100 PYs, overall and for PWIDs, respectively, in BC, following successful interferon-based therapy [20].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a review of low and high-risk HCV mono-infected patients also treated primarily with interferon-based therapies, estimated reinfection rates of 0.19 and 2.2 per 100 PYs, respectively, although estimates in these studies ranged considerably [17]. Additional studies have reported interferon era reinfection rates that range between 4.9 and 15.5 per 100 PYs for those with ongoing injection exposure following treatment [18,28,29]. We recently reported reinfection rates of 1.00 and 2.11 per 100 PYs, overall and for PWIDs, respectively, in BC, following successful interferon-based therapy [20].…”
Section: Discussionmentioning
confidence: 99%
“…Reinfection incidence in those individuals who used heroin and/or cocaine during follow-up was 8.7 per 100 py (95% CI 4.8, 23.7). In an Australian and New Zealand cohort of individuals treated for recent HCV infection (duration of HCV infection <18 months), ten cases of reinfection were identified in the population at risk (n = 120) [61]. Of the ten participants (seven HIV-positive MSM) with reinfection, eight reported injecting drug use during follow-up.…”
Section: Hcv Reinfection Among Hiv-positive Msmmentioning
confidence: 99%
“…The European NEAT study, including data from eight centres in Austria, France, Germany and the UK, reported an overall reinfection incidence of 7.3/100 person‐years in HIV‐positive MSM who spontaneously cleared their HCV infection, which occurs in approximately 15% of acute HCV infections in HIV‐positive MSM , or responded to treatment . These findings are in line with studies from Australia and elsewhere in Europe, showing that up to one‐third acquired a reinfection within two years . Temporal trends in the incidence of HCV reinfection have not been investigated, with exception of one recent study from Canada showing that reinfection rates did not diminish over time .…”
Section: Methodsmentioning
confidence: 72%